Indonesian manuscripts in Great Britain : a catalogue of manuscripts in Indonesian Languages in British Public Collections / M.C. Ricklefs, P. Voorhoeve, Annabel Teh Gallop - RICKLEFS, M.C; Voorhoeve, P.; Gallop, Annabel Teh (Yayasan Pustaka Obor Indonesia, 2014)
xxix, 349 hlm. : ilus. ; 23 cm.